Intratumoral heterogeneity of ERBB2 amplification and HER2 expression in micropapillary urothelial carcinoma - Isharwal, Sumit; Huang, Hongying; Nanjangud, Gouri; Audenet, François; Chen, Ying-Bei; Gopalan, Anuradha; Fine, Samson W.; Tickoo, Satish K.; Lee, Byron H.; Iyer, Gopa; Chadalavada, Kalyani; Rosenberg, Jonathan E.; et al. (Human pathology, 2018)
Micropapillary urothelial carcinoma (MPUC) is a rare but an aggressive variant of urothelial carcinoma. MPUC has been shown to commonly exhibit ERBB2 amplification and HER2 protein overexpression, but the frequency and distribution of these findings within micropapillary (MP) and not otherwise specified (NOS) components of tumors with mixed histology have not been addressed. Therefore, we evaluated ERBB2 amplification and HER2 expression in 43 MPUC cases by fluorescence in situ hybridization (FISH) and immunohistochemistry (IHC). Of the 35 tumors containing both MP and NOS components, ERBB2 amplification was present in both the MP and NOS components of 12 tumors (34.3%), in only the MP component of 11 tumors (31.4%), and exclusively in the NOS component of 4 tumors (11.4%). HER2 protein overexpression was significantly more commonly present in the MP component compared to the NOS component within the same tumor (68.6% versus 34.3%, P = .012). Overall, there was a moderately positive correlation between HER2 protein expression and ERBB2 amplification in both MP (ρ = 0.59, P < .001) and NOS (ρ = 0.70, P < .001) components. All MP/NOS areas with IHC score 3+ and none of MP/NOS areas with IHC score 0 were associated with ERBB2 amplification. We conclude that ERBB2 amplification and HER2 overexpression are preferentially but not exclusively identified in the MP component compared to the NOS component within the same tumor. Our findings identify the presence of intratumoral heterogeneity of ERBB2 amplification and HER2 expression in MPUC and provide grounds for further investigation into the mechanisms underlying the development of MPUC. •ERBB2 amplification is very common in micropapillary bladder cancer.•There is intratumoral heterogeneity of ERBB2 amplification in micropapillary bladder cancer.•ERBB2 amplification is more common in micropapillary component of tumors with mixed histology.